Implikasi Kejenuhan (Burnout) Belajar Terhadap Minat Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam Di SMP Negeri 2 Diwek Jombang - Moch. Sya’roni Hasan (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Abstract, boredom of learning is a condition where a person feels very tired, tired, and bored when the teaching and learning process is ongoing. This saturation is caused by various things, so that it gives various effects. So researchers focus on the problem and formulate it as follows: What causes burnout learn to students, how the impact of boredom learningon students' learning interest in PAI subjects, how is the solution to overcome the boredom of learning at SMPN 2 Diwek. The results of this study are: 1). Causes of boredom at SMPN 2 Diwek Jombang: Different Character of Students, Classroom Arrangement, Parental Pressure. Number of School Demands. 2). The impact of burnouton learning interest of students in PAI subjects can be seen from the behavior of students as follows: a). Negative Impact: Behavior to Attract the Attention of Others, Play mobile phones, Nosy and annoying friends, etc. b). Positive Impact: Makes children more proficient in worship, Awaken the spirit of students. 3). Solution to overcome burnout learning is as follows: inviting students to practice, using a habituation approach, using the story method by combining reality with existing theories, learning outside the classroom. Keyword: boredom of learning, interest in learning.